Bangladesh-Southeast Asia relations : some insights - Afroze, Shaheen; Bangladesh Institute of International and Strategic Studies (Dhaka : Academic Press and Publishers, 2002)
Proceedings of a seminar.
Includes bibliographical references.
Keywords: Southeast Asia -- Relations -- Bangladesh -- Congresses; Bangladesh -- Relations -- Southeast Asia -- Congresses